An improved user authentication protocol for wireless sensor networks. Issue 10 (13th September 2019) - Kaur, Damandeep; Kumar, Devender; Saini, Khushil Kumar; Grover, Harmanpreet Singh
Abstract: Wireless sensor networks (WSNs) have its applications in many domains such as agriculture, medicine, safety, and industry. Due to its wireless channel, it is vulnerable to many security threats. To provide end‐to‐end secure communication, various authentication and key agreement protocols have been discussed. Recently, Li et al have designed a mutual authentication and key agreement protocol for WSNs. However, it is found that this scheme does not resist to offline password guessing, device stolen, insider, and replay attacks besides user traceability problem. In this paper, a mutual authentication and key agreement protocol by overcoming the deficiencies of their scheme is proposed. Its formal security verification is shown using ProVerif tool. Its performance analysis is presented in terms of communication cost, computational cost, storage cost, and security features along with the other related schemes. It offers more security features than the other related schemes. Abstract : In this paper, cryptanalysis of Li et al.'s user authentication scheme for wireless sensor networks is done and it is found that it is vulnerable to the offline password guessing, device stolen, insider and replay attacks besides the user traceability problem. It is proposed an improved scheme by overcoming its drawbacks. Its formal security verification is shown using ProVerif tool. It is shown informally that it is resistant to the various known attacks and provides more security features.